2021
DOI: 10.21153/psj2020vol6no2art970
|View full text |Cite
|
Sign up to set email alerts
|

Coconuts, Custom-Play & COVID-19: Social Isolation, Serious Leisure and Personas in Animal Crossing: New Horizons

Abstract: This paper discusses Animal Crossing: New Horizons’ (ACNH) release during the COVID-19 pandemic, and draws upon responses from nearly 2000 players to frame how the game acts as a platform for routine substitution and social connectivity in a disconnected physical world. A combination of the game’s elements, including its comforting aesthetic, participatory community, financial mechanics, and goal-setting, promotes the player’s construction of their sense of self and provides crucial stability. In contrast to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Mom Flora described her AC:NH tasks as a “daily part of a routine that just helped soothe anxiety.” Dad Steve said that he “gravitated” toward the “predictability” of his daily tasks. This sense of routine has been found in other AC:NH studies (Barr & Copeland-Stewart, 2021), being the highest rated motivation for adult AC:NH players (Comerford, 2021).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Mom Flora described her AC:NH tasks as a “daily part of a routine that just helped soothe anxiety.” Dad Steve said that he “gravitated” toward the “predictability” of his daily tasks. This sense of routine has been found in other AC:NH studies (Barr & Copeland-Stewart, 2021), being the highest rated motivation for adult AC:NH players (Comerford, 2021).…”
Section: Resultssupporting
confidence: 78%
“…Indeed, individuals increased their use of mediated communication during the pandemic, which was beneficial for well-being (Brown & Greenfield, 2021; Gabbiadini et al, 2020). This included video games, which is not surprising, as the sociability affordance of video games is well documented (Jiow et al, 2017), even during the COVID-19 pandemic (Cmentowski & Krüger, 2020; Nebel & Ninaus, 2020), particularly with AC:NH (Comerford, 2021; Kleinman et al, 2021; Ng, 2021). We also note that other work has found that social aspects of video game play can enhance video game-related coping and recovery (Collins & Cox, 2014).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Family video game playing can provide routine ( Gee, Siyahhan, & Cirell, 2017 ). Playing AC:NH provided adults with a routine for pandemic coping ( Barr & Copeland-Stewart, 2021 ; Comerford, 2021 ; Kleinman et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple features of AC:NH make it a particularly good video game to facilitate coping. Animal Crossing games are described as leisurely and mundane ( Comerford, 2021 ; Khan, 2020 ; Kim, 2014 ; Straznickas, 2020 ; Zhu, 2020 ). Playing a game like AC:NH may be tied to some coping behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%